Correlation between seminal characteristics in Murrah bulls - Shukla, M s; Mishra, A K (The Indian Journal of Animal Sciences, 2005)
Evaculates (120) were taken from 3 bulls to study their neat semen quality. The overall average values of the 3 Murrah bulls for reaction time, semen volume, density, mass activity, progressive sperm motility, live sperm, sperm concentration, total abnormalities and hypo-osmotic swelling (%) in neat semen were 3.62± 0.29 min, 3.30± 0.10 ml, 3.39± 0.05,3.62± 0.04, 77.92± 0.33 %, 89.07± 0.44%, 1046.64± 34.21 million/ml, 12.57± 0.25% and 67.35± 0.57% respectively. Correlation study revealed a significant positive correlation of reaction time with semen volume. semen density with progressive sperm motility and sperm concentration and live sperm with semen density, progressive sperm motility and HOS%. Similarly. there was significant positive correlation between progressive sperm motility and sperm concentration and HOS%. However, total sperm abnormalities had significant negative corelation with HOS% (P&lt0.01) and progressive sperm motility and of live sperm per cent with per cent sperm abnormalities. In conclusion, this study revealed that some of the seminal characteristics of buffalo bulls are significantly correlated (positively or negatively) with each other.